Optimizing Co-parenting to Develop Entrepreneurial Personality in Children - Jenny Lukito Setiawan (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2017)
Over the course of her career as a psychologist, the writer has encountered a lot of problems in children, which when being explored further on, turned out to originate from problems related to parenting and marriage. On the other hand, throughout the years of being a lecturer, the writer has become convinced that it is essential for Indonesia’s young generation to have entrepreneurial personality characteristics in order to improve the nation’s competitiveness. Her experience as a psychologist and her journey as a lecturer have inspired the writer to explore marital and parenting problems, and how both of them can be worked on to facilitate the development of entrepreneurial personality characteristics in children, for the sake of nation’s advancement.